2018
DOI: 10.1080/01616412.2018.1446690
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of cardiac autonomic functions in myasthenia gravis

Abstract: These results suggest that sympathovagal balance has been disturbed in favour of sympathetic tone and that parasympathetic insufficiency has become more prominent. The current findings support the presence of cardiac autonomic involvement in patients with MG. The determination of cardiac autonomic function via noninvasive methods among patients with MG has high predictive value. The identification of autonomic dysfunction at an early stage and the early treatment of cardiovascular diseases can reduce morbidity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 29 publications
3
22
0
Order By: Relevance
“…Several previous studies have revealed sympathovagal imbalance in favor of sympathetic tone and decreased baroreflex in MG patients, which is in line with our results [ 13 , 38 , 46 ]. This sympathetic dominance could have resulted in significantly lower TFC values in MG patients than in the controls despite the decrease in the myocardial contractility parameters.…”
Section: Discussionsupporting
confidence: 93%
“…Several previous studies have revealed sympathovagal imbalance in favor of sympathetic tone and decreased baroreflex in MG patients, which is in line with our results [ 13 , 38 , 46 ]. This sympathetic dominance could have resulted in significantly lower TFC values in MG patients than in the controls despite the decrease in the myocardial contractility parameters.…”
Section: Discussionsupporting
confidence: 93%
“…In view of the risk of fatal cardiorespiratory arrest, simple HRV tests could be useful in COVID-19 patients for the sudden cardiac death risk. The disturbance in the baroreflex mechanism causes cardiac conduction abnormalities and the detection of an autonomic disorder via the evaluation of HRV and BRS using non-invasive methods in patients with COVID-19 could alert clinicians to possible patient morbidity and mortality (Kocabas et al, 2018). Prospective study needs are warranted to determine the value of autonomic testing and regimes for 4 https://www.ncbi.nlm.nih.gov/ (accessed March 19, 2021) 5 https://www.intechopen.com/books/subject/health-sciences (accessed March 19, 2021) 6 https://www.nemechekconsultativemedicine.com/vns-covid-19-white-paper/ (accessed March 19, 2021) the prevention and treatment of this complication of COVID-19 infection.…”
Section: Discussionmentioning
confidence: 99%
“…The study included all patients in a clinically stable condition that allowed testing using cardiovascular reflex tests. Patients with liver and renal disease; with systemic disease (e.g., connective tissue disorders); with a neurological disorder (e.g., cerebrovascular and Parkinson’s disease, Guillain–Barré syndrome, polyneuropathy, multiple sclerosis); with previously existing cardiac diseases (e.g., ischemic or congestive or valvular heart disease, cardiomyopathy, arrhythmia) ( Kocabas et al, 2018 ); patients with a malignancy; were excluded from the analysis. The 75 COVID-19 patients without associated diseases were divided into a severe group (45 patients with confirmed interstitial pneumonia, aged 51.27 ± 19.13, male 24, female 21) and mild group (30 patients, aged 41.56 ± 16.68, male 16, female 14 without pneumonia).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations